Performance Analysis of Three-Phase Interleaved Buck-Boost Converter in Wind Energy Maximum Power Point Tracking - Muhammad Qasim Nawaz Sciences; Wei Jiang Sciences; Aimal Khan Sciences (Al-Iraqia Journal for Scientific Engineering Research)
This paper presents a performance analysis of a three-phase interleaved buck-boost converter integrated with a Maximum Power Point Tracking (MPPT) algorithm using the Perturb and Observe (P&O) method for an independent wind energy generation system. The P&O method effectively identifies and tracks the maximum power point (MPP) under varying wind conditions. The use of a three-phase interleaved converter improves the power conversion efficiency and reduces input current ripple while distributing thermal stress across multiple phases. Simulation results, conducted via MATLAB, demonstrate a significant increase in overall system efficiency, with power extraction efficiency improving by up to 20% compared to traditional single-phase converters. The converter also reduces current ripple by approximately 30%, enhancing stability during variable wind profiles. The system responds accurately to wind speed changes, ensuring optimal energy extraction across various operational conditions. This study provides practical insights into the design and application of advanced power converters and MPPT controllers in wind energy systems, offering a pathway toward improved energy management and reliability in wind energy conversion systems.